The qualitative investigation: a communicative event (Revista Electrónica REDINE, 2018)
The communication distinguishes and characterizes the human being in an activity that links and orients the interpersonal relationship as a holistic process that interprets and transforms social interactions in everyday, there scenarios that the fundamental resource in all qualitative research is language, emotion and its communicative constructs, with the social actors to meet and change the environment of the human being.
Keywords: social interactions; interpersonal relationship; communicative constructs